Inter- and intramolecular reactions of dialkoxycarbenes - Venneri, Paul C. (My University, 2000)
This dissertation involved a study of the mechanistic and synthetic potential of nucleophilic carbenes in solution. More specifically, it deals with the inter- and intramolecular reactions of dialkoxycarbenes generated thermally from oxadiazoline precursors. Dialkoxy oxadiazolines (I ) decompose thermally via loss of N2 and acetone to afford dialkoxycarbenes (II ) (Scheme I). Dialkoxycarbenes are singlet carbenes which possess nucleophilic character because of heteroatom electron donation into the vacant p -orbital of carbon. This is best illustrated by writing the dipolar resonance contributor (II ) with formal negative charge at the carbene carbon and formal positive charge on oxygen. This special property of dialkoxycarbenes allows them to take part in a wide variety of chemical reactions including fragmentations, and inter- and intramolecular additions. The first section of the dissertation describes the first example of a dialkoxycarbene fragmentation to radical pairs in solution in which both the carbene and the radicals could be trapped. Thermolysis of cinnamyloxymethoxy oxadiazoline (III ) afforded the corresponding dialkoxycarbene (IV ) which fragmented to methoxycarbonyl radical (V ) and phenylallyl radical (VI ) (Scheme II). The second section describes the use of dimethoxycarbene as a convenient synthetic tool for the ring expansion of strained cyclic carbonyl compounds. Thermolysis of dimethoxy oxadiazoline (VII ) afforded dimethoxycarbene (VIII ), which in the presence of carbonyl compounds (IX ) yielded products (X ) of formal carbene insertion in-between the carbonyl group and the alpha carbon atom (Scheme III). In unsymmetrical carbonyl-containing compounds, carbene insertion was selective, favouring insertion in-between the carbonyl group and the most electron-rich alpha carbon. The final section highlights advances in the area of intramolecular dialkoxycarbene additions to alkynes. In particular, a preliminary investigation into the area of tandem carbene cyclizations is discussed. This work involved the synthesis and thermolysis of dialkoxy oxadiazolines containing two tethered alkyne units. It was envisioned that intramolecular carbene addition to one alkyne unit would afford a vinyl carbene (XI ) which could add to a second alkyne tether to yield a second vinyl carbene (XII ) (Scheme IV). This methodology has the potential for synthesis of multicyclic systems in a one-pot reaction.
Keywords: Chemistry; Chemistry